Hybrid Traction System for a Haulage Locomotive for Industrial Quarry Railways - Riabov, Ie. S.; Yeritsian, B. Kh.; Tykhonov, A. S.; Khazov, O. A. (Science and Transport Progress, 2025)
Purpose. The article aims to determine the parameters of a hybrid traction system for a diesel locomotive for haulage work on industrial quarry railways. Methodology. The study was carried out on the example of a section of the quarry railroad of the Northern Mining and Processing Plant. It is shown that in order to determine the parameters of the traction system, it is necessary to take into account the work in the traction and braking systems for the freight and empty semi-trains. The calculations were performed using the provisions of the theory of locomotive traction. Findings. It has been determined that on a given track profile with a maximum elevation of 35 ‰, a two-section twelve-axle diesel locomotive can drive a train with 12 loaded cars (dump cars). The speed is 10 km/h, and the power output is about 2,400 kW. To ensure the braking of a loaded train on the studied route (the largest slope (downhill) is 28 ‰), the tangential power should be 3,000 kW, and the movement will be carried out at a speed of 15 km/h. It is proposed to use a hybrid traction system, the power plant of which includes an energy storage device. To ensure high traction properties, it is necessary to use a traction electric drive based on AC motors. When using traction asynchronous electric motors, it is possible to use bogie power supply and control of electric motors, which will ensure high traction properties of the locomotive. The expediency of equipping the locomotive with devices that provide its power supply from the contact network while moving along electrified sections is shown. A 3D sketch of the hybrid traction system equipment placement on the 2TE10M diesel locomotive was developed. To develop the sketch, models of an 800 kW diesel generator set and a 500 kWh energy storage device with a peak capacity of 1,000 kW were used. Originality. The parameters of a dual-mode locomotive equipped with a hybrid traction system and designed for haulage operations on industrial quarry railways have been determined. Practical value. The obtained results can be used in the development of projects for the modernization of diesel locomotives and the creation of new traction rolling stock for quarry and mainline railways.